Efektivitas Penerapan E-Litigasi Terhadap Proses Penyelesaian Perkara Perceraian; Studi Kasus di Pengadilan Agama Donggala Kelas IB - Wahyuni, Sri; Yamani, Gasim; Malarangan, Hilal (Lembaga Teewan Journal Solutions, 2026)
This study analyzes the effectiveness of the implementation of e-litigation in divorce case settlement processes at the Donggala Religious Court Class IB. Employing an empirical legal research design with a qualitative descriptive approach, data were gathered through comprehensive interviews with judges, court advocates, and litigants. The analysis utilizes Lawrence M. Friedman's legal system theory, focusing on legal structure, substance, and culture. The results demonstrate that the e-litigation framework significantly streamlines the judicial workflow, reducing physical attendance requirements and accelerating administrative timelines. However, systemic structural constraints persist, notably intermittent network infrastructure stability and disparate levels of digital literacy among litigants. Culturally, while legal professionals exhibit high adaptive alignment, rural litigants still heavily require persistent manual mediation, indicating that comprehensive electronic litigation is effective yet demands infrastructural reinforcement.